The Impact of Islamic Thought on Creating Space in the Residence: Case Study of Suhaimi’s and Sibai’s Houses - alsarhan, Duha Suliman (مجلة الشرق الأوسط للعلوم الإنسانية والثقافية, 2024)
This study investigates the factors influencing Islamic residence design, with a focus on understanding the cultural, religious, environmental, and socio-economic considerations that shape architectural practices in Islamic communities. Through a multidisciplinary approach, the research examines the interplay between Islamic beliefs, functional requirements, historical heritage, and contemporary design principles in the creation of residential spaces that reflect Islamic values and traditions. Drawing on architectural analysis, case studies and corpus analysis, the study identifies key factors influencing Islamic residence design, including cultural and religious beliefs, functional requirements, climate adaptation, architectural heritage, sustainability, and socio-economic dynamics. The findings highlight the importance of integrating Islamic principles into residential design, engaging with local communities, promoting sustainable practices, preserving architectural heritage, and advancing research and education in the field of Islamic architecture. The study contributes to a deeper understanding of Islamic residence design and provides valuable insights for architects, designers, policymakers, and researchers seeking to create culturally sensitive and contextually appropriate residential environments in Islamic communities.